2019
DOI: 10.2166/wcc.2019.036
|View full text |Cite
|
Sign up to set email alerts
|

Drought and climate change assessment using Standardized Precipitation Index (SPI) for Sarawak River Basin

Abstract: Severe droughts in the year 1998 and 2014 in Sarawak due to the strong El Nino has impacted the water supply and irrigated agriculture. In this study, the Standardized Precipitation Index (SPI) was used for drought identification and monitoring in Sarawak River Basin. Using monthly precipitation data between the year 1975 and 2016 for 15 rainfall stations in the basin, the drought index values were obtained for the time scale of three, six and nine months. Rainfall trend for the years in study was also assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Following this, the World Meteorological Organization reported that droughts have hit Sarawak numerous times since the 1970s due to a great decrease in rainfall associated with El Niño events [66]. It has also been predicted that droughts will hit Sarawak harder and for more prolonged periods in the future [67] with an expected increase temperature of 3.8 • C [68]. Judging from future climate change projections, the capacity of these communities to adapt to future climate stressors will be further challenged.…”
Section: Discussionmentioning
confidence: 99%
“…Following this, the World Meteorological Organization reported that droughts have hit Sarawak numerous times since the 1970s due to a great decrease in rainfall associated with El Niño events [66]. It has also been predicted that droughts will hit Sarawak harder and for more prolonged periods in the future [67] with an expected increase temperature of 3.8 • C [68]. Judging from future climate change projections, the capacity of these communities to adapt to future climate stressors will be further challenged.…”
Section: Discussionmentioning
confidence: 99%
“…Sen's slope estimator is commonly used with the MK test; the two parameters are widely used in detecting trends of variables in meteorology and hydrology fields [12].…”
Section: Mann-kendall Test and Sen's Slopementioning
confidence: 99%
“…For this, numerous indices have been put forward by researchers. Some of them are, the Palme Drought Severity Index (PDSI) [12], Surface Water Supply Index (SWSI) [13], Palfai Aridity Index (PAI) [14], Standardized Precipitation Index (SPI) [15,16], and Standardized Precipitation Evapotranspiration Index (SPEI). The examination through any of above indices is subject to the essence of the index, local surroundings, accessibility of facts and rationality [17].…”
Section: Introductionmentioning
confidence: 99%